On the study of flow between unsteady squeezing rotating discs with cross diffusion effects under the influence of variable magnetic field. Issue 11 (November 2018) - Shah, Rehan Ali; Khan, Aamir; Shuaib, Muhammad
Abstract: The aim of this article is to provide an analytical and numerical investigation to the viscous fluid flow, heat and mass transfer under the influence of a variable magnetic field. The governing system of partial differential equations are transformed by means of similarity transformations to a system of ordinary differential equations which are solved by Homotopy Analysis Method (HAM) and BVP4 c . The effects of involved physical parameters are illustrated for the velocity components, magnetic field components, heat and mass transfers. Authentification of HAM results for various involved physical parameters are supported by comparison with numerical results obtained by BVP4 c . It is observed that increasing distance between discs increase pressure on lower disc and torque on upper disc. It is also observed that increase in axial component of magnetic field increase fluid's axial velocity and increase in magnetic Reynold's number decrease magnetic flux it lower disc. Heat flux from lower to upper disc is increased by increase in Dufour number.